SUBTITUSI TEPUNG TAPIOKA ( Manihot esculenta ) DALAM PEMBUATAN DODOL - Indra Tangketasik; Thelma D.J. Tuju; Tineke M. Langi (COCOS, 2013)
ABSTRACTCassava is a tuber crop that contains a lot of starch. This type of plant is widely cultivated Indonesian society both small and large scale, known as the producer of cassava flour with a very high carbohydrate production. Most of the carbohydrates produced by the plant is cassava starch. This study aims to determine the substitution of cassava flour in making lunkhead who liked / accepted by the panelists. The results showed that 10% substitution of glutinous rice flour and tapioca flour 90% most panelists favored with moisture content 26.14% and total sugars 21,41%.Keywords : Tapioca Flour, Glutinous Rice Flour, Dodol